Losing One's Head or Gaining a New Body?. Issue 2 (18th April 2022) - Eberl, Jason T
Abstract: A surgical head-transplant technique, HEAVEN, promises to offer significantly improved quality of life for quadriplegics and others whose minds are functional, but whose bodies require artificial support to continue living. HEAVEN putatively actualizes a thought-experiment long debated by philosophers concerning the definition of personhood and criterion of personal identity through time and change. HEAVEN's advocates presume to preserve the identity of the person whose head is transplanted onto another's living body, leaving one's previous body behind as one would their corpse. Various classical and contemporary theories of personhood and personal identity would support this presumption, while others would contest it as providing an accurate or complete view of what is essential for a human person to persist through this procedure. This paper brings such theories to bear in analyzing whether HEAVEN can indeed deliver on its promise of complete ontological survival for the person whose head is transplanted.